2017
DOI: 10.1186/s12943-017-0712-x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Hepatocellular carcinoma: implications for genomic and immune therapies

Abstract: Hepatocellular carcinoma (HCC), the most common type of primary liver cancer, is a leading cause of cancer-related death worldwide. It is highly refractory to most systemic therapies. Recently, significant progress has been made in uncovering genomic alterations in HCC, including potentially targetable aberrations. The most common molecular anomalies in this malignancy are mutations in the TERT promoter, TP53, CTNNB1, AXIN1, ARID1A, CDKN2A and CCND1 genes. PTEN loss at the protein level is also frequent. Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
263
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(273 citation statements)
references
References 113 publications
(152 reference statements)
8
263
0
2
Order By: Relevance
“…There were 745,500 deaths in 2012 and 782,500 new cases are diagnosed globally, and China alone accounts for over 50% of the total cases [1,2]. Hepatocellular carcinoma (HCC) is the most common liver cancer and approximately 90% of primary liver cancer [3]. In addition, HCC is one of the most lethal malignancies due to its complexities, high metastasis and recurrence and limited treatment options [4].…”
Section: Tcf19 Enhances Cell Proliferation In Hepatocellular Carcinommentioning
confidence: 99%
“…There were 745,500 deaths in 2012 and 782,500 new cases are diagnosed globally, and China alone accounts for over 50% of the total cases [1,2]. Hepatocellular carcinoma (HCC) is the most common liver cancer and approximately 90% of primary liver cancer [3]. In addition, HCC is one of the most lethal malignancies due to its complexities, high metastasis and recurrence and limited treatment options [4].…”
Section: Tcf19 Enhances Cell Proliferation In Hepatocellular Carcinommentioning
confidence: 99%
“…The complexity of molecular events implicated in hepatocellular carcinoma progression is directly associated with its various etiologies that differently contribute to tumor initiation, growth and evasion. During last decades, multiscale omics data analysis of genome and proteome allowed to explore molecular networks associated with HCC and mathematical models have been developed namely to predict cancer [4] Id: M5890, available at http://software.broadinstitute.org/gsea/msigdb/geneset_page.jsp? geneSetName=HALLMARK_TNFA_SIGNALING_VIA_NFKB cell behavior [34].…”
Section: Discussionmentioning
confidence: 99%
“…For that purpose, we take advantage of the NFκB-dependent signature available in MSigDB [22,30]. We selected the HALLMARK TNFA SIGNALING VIA NFKB [4] signature which contains 200 genes regulated by NFκB in response to TNF. As shown in Additional file 1: Figure S7A, we demonstrated that these genes were more expressed in high aggressive HCC when compared with low aggressive ones supporting the activation of NFκB signaling.…”
Section: Activation Of Nfκb Signaling In Aggressive Hccmentioning
confidence: 99%
“…Studies show that the genetic and epigenetic changes of several critical genes were associated with the development of liver cancer. 31,32 The telomerase reverse transcriptase (TERT) gene promoter mutation is a common somatic genetic variant in HCC, which is present in 50% of HCC patients. 33 Telomere reverse transcriptase is an enzyme that is necessary for telomere elongation and preventing cell damage.…”
Section: Liver Cancer Related Somatic Mutationsmentioning
confidence: 99%
“…ARDI1A mutation reduces the transcription of tumor suppressor genes and increases the risk of HCC. 31,32 Studies showed that loss function of ARDI1A gene is associated with the development of many cancers such as kidney cancer, liver cancer and breast cancer. Further analysis also showed that ARDI1A gene mutation was located at the opposite stand of the genome to that of TP53 gene mutation, indicating that both ARDI1A and TP53 may jointly inhibit tumor formation.…”
Section: Liver Cancer Related Somatic Mutationsmentioning
confidence: 99%